Indian Journal of Physics and Proceedings of the Indian Association for the Cultivation of Science - Indian Association for the Cultivation of Science; Indian Association for the Cultivation of Science; Indian Physical Society (Calcutta Indian Association for the Cultivation of Science, 1926)
Vols. 1-9 include the association's annual report for 1925-34.
Keywords: Science -- Periodicals; Physics -- Periodicals